2018
DOI: 10.5588/pha.17.0080
|View full text |Cite
|
Sign up to set email alerts
|

Unsuccessful Xpert® MTB/RIF results: the Nigerian experience

Abstract: Setting: Nigeria, a high tuberculosis (TB) burden country. Objective: To study the rate, distribution and causes of unsuccessful Xpert ® MTB/RIF test outcomes, with the aim of identifying key areas that need to be strengthened for optimal performance of the assay. Design: This was a retrospective analysis of data uploaded between January and December 2015 from Xpert facilities to the central server using GXAlert. Result: Of 52 219 test results uploaded from 176 Xpert machines, 22.5% were positive for Mycobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 17 publications
1
28
4
1
Order By: Relevance
“…Poor performance in this testing procedure is mainly due to technical errors and non-adherence to standard operational procedure. 17 Disputed cases need repeat-testing and frequent transfer to referral laboratories for further tests and culture. There also remains a case for clinical suspicion of TB and therapeutic trial of anti TB drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Poor performance in this testing procedure is mainly due to technical errors and non-adherence to standard operational procedure. 17 Disputed cases need repeat-testing and frequent transfer to referral laboratories for further tests and culture. There also remains a case for clinical suspicion of TB and therapeutic trial of anti TB drugs.…”
Section: Resultsmentioning
confidence: 99%
“…It provides results fast (ideally within 2-4 h) compared to the 4-6 weeks of traditional bacteriological culture [1]. Despite the potential of Xpert® to improve case detection of TB, several studies, including those undertaken in Kenya, have shown that adoption and utilisation has been low [2][3][4][5]. Kenya introduced Xpert® in 2011 and now has over 156 machines, with more coming, including the newer improved Ultra® [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study from Peru (a high TB burden, low-resource setting) also identi ed constraints to diagnosing TB in children related to ignorance and stigma; limited access to diagnostic tests; inadequately trained health centre staff; and provider shortages [13]. While several studies have highlighted the challenges of implementing Xpert® among adults, data addressing constraints to the use of this diagnostic among children are sparse [3,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%